2012
DOI: 10.1152/ajpendo.00159.2012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vertical sleeve gastrectomy in melanocortin receptor 4-deficient rats

Abstract: Bariatric surgery is currently the most effective treatment for obesity. Vertical sleeve gastrectomy (VSG), a commonly applied bariatric procedure, involves surgically incising most of the volume of the stomach. In humans, partial loss of melanocortin receptor-4 (MC4R) activity is the most common monogenic correlate of obesity regardless of lifestyle. At present it is unclear whether genetic alteration of MC4R signaling modulates the beneficial effects of VSG. Following VSG, we analyzed body weight, food intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 26 publications
4
44
0
1
Order By: Relevance
“…Most of the recent animal studies and some studies in humans have examined the role of the melanocortin system, which seems to be central to many peripheral and brain-derived stimuli that control eating and body weight (55,92,93,157). In humans, the sufficiency of one functional MC4r gene for effective RYGB outcome was indicated in some studies, including RYGB or VSG-operated humans (157).…”
Section: Cns Eating and Body Weight Controls After Rygbmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the recent animal studies and some studies in humans have examined the role of the melanocortin system, which seems to be central to many peripheral and brain-derived stimuli that control eating and body weight (55,92,93,157). In humans, the sufficiency of one functional MC4r gene for effective RYGB outcome was indicated in some studies, including RYGB or VSG-operated humans (157).…”
Section: Cns Eating and Body Weight Controls After Rygbmentioning
confidence: 99%
“…While homozygous and heterozygous melanocortin-4 receptor (MC4r) knockout rats appeared to be fully responsive to weight-reducing VSG surgery (93), homozygous MC4r knockout mice lost less weight after RYGB than heterozygous knockout or wildtype mice (55).…”
Section: Cns Eating and Body Weight Controls After Rygbmentioning
confidence: 99%
“…With the exception of a few rare variants, 35 all studies looking at patients with MC4R variants found that gastric bypass surgery was fully effective. 14,33,35,36 However, gastric banding in one rare patient with complete loss of MC4R functionality did not produce a lasting reduction in body weight.…”
Section: Potential Underlying Mechanisms For Change In Set Pointmentioning
confidence: 88%
“…11 As shown earlier, 12 SHU9119 powerfully stimulates food intake and over a 2-week infusion period results in significant weight gain and obesity in normal, chow fed as well as high-fat fed rats, 11 reminiscent of rats and mice with MC4R deficiency. 13,14 Importantly, when the antagonist infusion was halted, rats gradually returned to their pre-infusion body weight, thus demonstrating the concept of defense of their lower body weight. We thus used this approach to test whether rats that had settled at a lower body weight about 3 months after RYGB surgery would show a similar behavior.…”
Section: Behavioral Evidence For Rygb-induced Change In Defended Bodymentioning
confidence: 90%
See 1 more Smart Citation